Minimally invasive beating heart full coronary artery bypass in a patient with pancreatic ductal adenocarcinoma - Şahin, Mazlum (The European Research Journal, 2019)
There are various problems associated with cardiopulmonary bypass in cardiac operations of patients with cancer. Our patient was a 73-year-old male patient diagnosed with pancreatic ductal adenocarcinoma. Coronary angiography of the patient who was planned to undergo tumor surgery revealed severe anomalies extending to the proximal of the diagonal 1 at the left anterior descending artery osteal and diagonal 1 distinction. Minimally invasive off-pump direct coronary artery bypass was performed in the patient. The patient was discharged on the 4th postoperative day and he was operated with the cause of pancreatic cancer at the third week. We think that minimally invasive coronary bypass without cardiopulmonary bypass can be performed with delayed prevention of cancer treatment and faster healing in patients with cancer of various systems.